S96 A combination score of raised sACE, lymphopenia and hypergammaglobulinaemia correlates with active disease on thoracic CT scan of patients with pulmonary sarcoidosis. (19th November 2012) - Kendrick, YR; Helm, EJ; Benamore, R; Ho, LP
Abstract : Introduction: Clinical decisions about treatment in pulmonary sarcoidosis, and phenotyping research studies are hampered by inability to objectively measure disease activity. We reviewed 120 consecutive patients from our Sarcoidosis Clinic and observed that raised sACE, immunoglobulin and/or presence of lymphopenia were associated with clinical decisions to change treatment. We question if these markers could be combined to form an objective measure of disease activity in pulmonary sarcoidosis. Methods: As there is no 'gold standard' for disease activity in sarcoidosis, we used thoracic CT scan to reflect disease activity on the basis that ground glass opacity, nodularity, consolidation, interlobular septal thickening and conglomeration reflect T cell alveolit is, cellular infiltrate and granulomatous deposits1–2. Using Fleischner Society definition of terms3, we designed a scoring system ("CT activity score; CTAS") to quantify this, and examined if a composite clinical score ("clinical activity score; CAS"; IgG>13 g/l= 1, Lymphocytes <1x10^9/l = 1, sACE <55 U/l = 0, 56–100 U/l = 1, >100 U/l = 2) correlated with changes in CTAS. An enhanced CAS incorporating extent of defined CXR abnormalities was also examined. We collected data from 100 consecutive patients diagnosed according to WASOG/ATS criteria (with histological confirmation), who had thoracic CT scan, CXR and blood parameters within three months of each other. Two radiologists scored the CT scans blindly. We present results for the first 20 cases. Results: CTAS score (maximum possible 81) in our patients ranged from 0 to 40; CAS from 0–4 (maximum 5); when including CXR score - from 1–12 (maximum 12). We found a strong correlation between CAS and CTAS (Figure 1). No correlation was observed between the CTAS and FVC, TLCO or KCO, supporting the premise that severe irreversible functional loss can be inactive. Conclusions: A combination score incorporating lymphopenia, sACE levels, and hypergammaglobulinemia is strongly correlated with CT quantification of disease activity in pulmonary sarcoidosis. Addition of CXR scoring improved the correlation. This score could be used as an indicator of disease activity to aid clinical decisions on treatment, and paves the way for collation of larger numbers and longitudinal studies to further validate the tool. References: Nishimura K et al. Radiology 1993. Oberstein A et al. Sarc Vasc Diffuse Lung Dis 1997. Hansell DM et al. Radiology 2008.